Does treatment with antidepressants, antipsychotics, or benzodiazepines hamper allergy skin testing?. Issue 7 (6th September 2021) - Kjaer, Henrik Fomsgaard; Mortz, Charlotte Gotthard; Bindslev‐Jensen, Carsten
Abstract: Background: Treatment with commonly used drugs such as antidepressants (ADs), antipsychotics (APs), and benzodiazepines (BDs) may hamper the use of allergy skin testing due to possible antihistaminic effects. Objective: To examine the antihistaminic effect of AD, AP, and BD as measured by the ability of these drugs to suppress the normal wheal reaction caused by skin prick test (SPT). Methods: Skin prick test was performed in patients receiving treatment with AD, AP, and/or BD. Double SPT was performed with histamine solutions of 10, 30, and 100 mg/ml and mean wheal diameter calculated. Results: A total of 313 patients were included. 236 (75%) patients were treated with one of the examined drugs and 77 (25%) patients with more than one of these drugs. Drugs most frequently used was sertraline ( n  = 65), citalopram ( n  = 63), mirtazapine ( n  = 36), venlafaxine ( n  = 33), and quetiapine ( n  = 32). Treatment with mirtazapine and/or quetiapine was associated with negative SPTs in 30/36 (83%) and 22/32 (69%), and the antihistaminic effect of these drugs was dose‐dependent. For patients treated with selective serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCAs), serotonin norepinephrine reuptake inhibitors (SNRIs), or BD alone, almost all SPTs were positive (94%, 95%, 100%, and 100%, respectively). Negative SPTs in patients treated with SSRI, TCA, SNRI, or BD and ≥1 other of the examined drugs were associated with simultaneous treatment with mirtazapine or quetiapine in 39/44 (89%) patients. Conclusion: Skin testing has little meaning in patients treated with mirtazapine or quetiapine. Treatment with SSRI, SNRI, and BD does not seem to affect the results of SPTs, whereas skin tests in patients treated with TCA should be interpreted with caution.